Effects of different vibration exercises on bench press - Marin, P. J.; Torres-Luque, G.; Hernandez-Garcia, R.; Garcia-Lopez, D.; Garatachea, N. (International Journal of Sports Medicine, 2011)
This study was undertaken to analyze the effects of different vibration recovery strategies via feet or hands on the number of repetitions performed and on mean velocity, peak velocity and blood lactate concentration during consecutive bench-press sets. 9 elite judo athletes performed 3 sets of bench press at 60% of one-repetition maximum (1RM), leading to failure and allowing a 180 s rest period between sets. During the rest period, 1 of the 3 following procedures was performed: 150 s rest plus 30 s push-up vibration exercise (Push-up), 150 s rest plus 30 s squat vibration exercise (Squat) or 180 s only rest (Passive). Statistical analysis revealed that the Squat condition resulted in a significant increase in the number of repetitions achieved, in comparison with all other rest strategies. However, kinematic parameters and blood lactate concentration were not affected by vibration. These data suggest that a vibration stimulus applied to the feet, between sets, can result in positive improvements in upper body resistance exercise performance. Although the mechanisms are not fully understood, this positive effect of vibration could be due to an increased motor cortex excitability and voluntary drive.